Characterization of Infectious Bursal Disease Virus Isolated In Malaysia for the Development of Diagnostic Tools - Phong, Su Fun (2002)
The P97/302 field outbreak isolate was identified as a very virulent infectious bursal disease virus (vvIBDV) of serotype 1, based on the conventional and molecular characterization methods. The high mortality, gross and histopathological lesions observed during the outbreak and in the experimental infected SPF chickens induced by P97/302 IBDV isolate were characteristics of vvIBDV strain reported previously. The sequence of P97/302 isolate has amino acid substitutions at 222(A), 256(1), 294(1) and 299(S) similar to other reported vvIBDV. This isolate does not have 249(K) and 2S4(S) amino acid residues which have been reported to be present in variant strains. The amino acid residues of the P97/302 at the two hydrophilic regions and the serine-rich heptapeptide region are the same as reported for vv strains of UK661, HK46 and OKYM. The P97/302 IBDV isolate can be digested with Taq 1, Acel, Sty 1, Spel enzymes and not with Sac1 as reported for other vvIBDV. This isolate is most homologous to the reported vvIBDV strains especially UK661. Phylogenetic analysis based on the nucleotide sequence of the hypervariable region revealed that P97/302 IBDV isolate can be clustered with the vvIBDV strains and is distinct from classical, variant and attenuated strains. Using this P97/302 IBDV local isolate, the study has successfully developed three diagnostic tools for antibody and antigen detection. They are the indirect, double antibody sandwich (DAS) and reversetranscription (RT) nested polymerase chain reaction (PCR) enzyme-linked immunoassay assay (ELISA). The developed indirect and DAS ELISA are based on the use of regression equation line which generated from the standard curves to measure IBD antibody titre. They are highly significant correlated (p<0.01) when compared with IDEXX commercial ELISA. They are more advantage than the commercial kits whereby the local isolate was used for the ELISA coating which was able to enhance the accuracy to predict the protection to IBD. The developed DAS ELISA for antigen detection is also highly specific. The developed RT nested PCR was highly specific and ten times more sensitive when compared to conventional RT/PCR. The RT nested PCR ELISA method was also highly specific and hundred times more sensitive when compared to conventional RTIPCR with agarose gel electrophoresis detection method. It was concluded that the P97/302 local isolate was vvIBDV strain and the developed indirect, DAS and RT nested PCR ELISA are potentially used for monitoring and screening large number of samples for antibody and antigen detection from chicken flocks.